An Introduction to Formal Logic - Magnus, P.D.; Open Textbook Library (Open Textbook Library, 2012)
forall x is an introduction to sentential logic and first-order predicate logic with identity, logical systems that significantly influenced twentieth-century analytic philosophy. After working through the material in this book, a student should be able to understand most quantified expressions that arise in their philosophical reading. This books treats symbolization, formal semantics, and proof theory for each language. The discussion of formal semantics is more direct than in many introductory texts. Although forall x does not contain proofs of soundness and completeness, it lays the groundwork for understanding why these are things that need to be proven. Throughout the book, I have tried to highlight the choices involved in developing sentential and predicate logic. Students should realize that these two are not the only possible formal languages. In translating to a formal language, we simplify and profit in clarity. The simplification comes at a cost, and different formal languages are suited to translating different parts of natural language. The book is designed to provide a semester's worth of material for an introductory college course. It would be possible to use the book only for sentential logic, by skipping chapters 4-5 and parts of chapter 6.
Chapter 1: What is logic? -- Chapter 2: Sentential logic -- Chapter 3: Truth tables -- Chapter 4: Quantified logic -- Chapter 5: Formal semantics -- Chapter 6: Proofs
In English.
Description based on print resource
Keywords: Humanities -- Textbooks; Philosophy -- Textbooks